Poder judiciário e consequencialismo: o caminho para o capitalismo constitucional - Rossini, Luiz Felipe (2024)
This doctoral thesis investigates the protection of fundamental rights, without prejudice to the bases of the capitalist system, through the activity carried out by the Judiciary, focusing on the appreciation of judicial precedents, and the adoption of consequentialism as an element to guide the decisions made by the various bodies that make up the judiciary. The theme acquires extreme relevance in a globalization scenario, with large transnational companies assuming the leading role in social and economic relations around the world, especially in late developing countries, such as Brazil. In this context, the research examines the historical evolution and the different theories that tried, without success, to find a point of balance between the interest of market agents in capitalism and the fundamental rights of each individual, highlighting the Jus naturalist and Jus positivist attempts, the role of humanism and the different meanings of the term, in addition to utilitarianism and the failure of the socialist attempt. Legal institutes in the common law and civil law systems are examined, and the tendency towards rapprochement between the two, the role of precedents in each of them, to delve deeper into what our legal system in Brazil today is based on. Finally, the research proposes recommendations and reflections for the adoption of the proposed model, and counterweights to prevent arbitrariness and judicial activism, always with a view to predictability of decisions, and security in protecting what is most important to the individual: your dignity.